The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0743558414550246
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Explanations for the Exclusion of Peers With Mental Health Problems

Abstract: Young people with mental health problems are often excluded from their peer group; however, research has not specifically explored their peers’ explanations for this exclusion. Drawing on data from group interviews with Irish adolescents (N = 148), this study explores the reasons offered for rejecting young people with mental health problems. Such reasons include perceived violation of expectations of friendships, and perceived social and personal risks to members of the peer group. The implications of these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
(47 reference statements)
1
19
0
2
Order By: Relevance
“…58 Especially for adolescents, for whom peer acceptance is important during this developmental stage, mental illness is perceived to incur personal and social risks, leading to the stigmatization of the mentally ill adolescent. 59 Our results suggest that the participants' knowledge of depression is associated with their attitude toward getting help. This is similar to findings from Schmidt et al, 60 Spagnolo et al, 61 and Strunk et al 62 Information related to the biological and neurological origins of mental illness, especially, may lead the public to be more open to seeking medical help for their condition.…”
Section: Discussionmentioning
confidence: 66%
“…58 Especially for adolescents, for whom peer acceptance is important during this developmental stage, mental illness is perceived to incur personal and social risks, leading to the stigmatization of the mentally ill adolescent. 59 Our results suggest that the participants' knowledge of depression is associated with their attitude toward getting help. This is similar to findings from Schmidt et al, 60 Spagnolo et al, 61 and Strunk et al 62 Information related to the biological and neurological origins of mental illness, especially, may lead the public to be more open to seeking medical help for their condition.…”
Section: Discussionmentioning
confidence: 66%
“…La mejora inicial de las actitudes que se informa en algunos estudios puede tener poco poder predictivo sobre las conductas estigmatizantes o discriminatorias que podrían quedar inalteradas en un nivel más implícito. De hecho, algunos autores argumentan que la existencia de actitudes implícitas no adecuadamente medidas puede estar contaminando buena parte de los resultados encontrados en las investigaciones sobre el estigma en el contexto escolar (González-Sanguino, Muñoz, Castellanos, Pérez-Santos y Orihuela-Villameriel, 2019;O'Driscoll et al, 2012;O'Driscoll, Heary, Hennessy y McKeague, 2015a;Silke et al, 2017). Formatos muy cortos quizá logren cambios actitudinales explícitos, pero van a tener un efecto muy recortado sobre los estereotipos y prejuicios básicos hacia la enfermedad mental (Ke et al, 2015) por lo que, a nuestro juicio, es necesario optar por intervenciones más globales y extensivas para optimizar los rendimientos.…”
Section: Discussionunclassified
“…The study presented by O’Driscoll, Heary, Hennessy, and McKeague (2015) took place in Ireland and investigated the ways that adolescents with mental health problems are excluded by peers. Using vignettes of adolescents with attention deficit hyperactivity disorder (ADHD) or depression, they found that reasons for excluding peers with these problems centered on two themes, reciprocity and risk.…”
Section: The Special Section: Expanding Research On Cultural Variatiomentioning
confidence: 99%